Acid-Alkaline Treatment of Mordenite and Its Catalytic Activity in the Hydrotreatment of Bio-Oil - Febi Yusniyanti; Wega Trisunaryanti; Triyono Triyono (Indonesian Journal of Chemistry, 2021)
Acid-alkaline treatment using acetic acid and sodium hydroxide (NaOH) were applied on mordenite (MOR) to increase the Si/Al ratio and surface area properties. Various time treatment (3, 6, and 9 h) and concentration of acetic acid (6, 9, and 12 M) were used to treat MOR, and followed by the treatment with NaOH (0.1 M) under room temperature. The MOR and treated mordenite were applied as a catalyst for hydrotreatment of cellulose-derived bio-oil. The acetic acid treatment caused the increase of the Si/Al ratio of mordenite up to 27.03. The Si/Al ratio was determined using ICP-AES analysis which was also confirmed using FT-IR analysis. The acidity was determined using NH3 vapors adsorption. The acidity test revealed that as the Si/Al ratio increased the acidity of mordenite decreased. The advantage of using acetic acid for acid treatment was that the XRD patterns of mordenite can be preserved with a little decrease of the intensity. On the other hand, the NaOH treatment under room temperature decreased the crystallinity down to 68%, which was calculated using XRD. The acid-alkaline treatment of mordenite succeeded to increase the surface area 2 times larger than the parent mordenite. The surface area was obtained from BET analysis. The acid-alkaline treated mordenite exhibited better catalytic activity upon hydrotreatment of biomass-derived bio-oil compared to the parent mordenite which corresponded to its highest surface area.